Analyze and Record a series of Purchase Transactions on Companies using Online Accounting Software - Sunarya, Po. Abas; Nawi, Mohd Nasrun Mohd; Rahayu, Sri (APTISI Transactions on Management (ATM), 2017)
One of the financial activities in the company is to record a series of every purchase transaction which serves to record every fund issued by the company that creates liabilities or debts to the supplier. This is also equally important that must be considered with other recording activities because if the expenditure is not recorded properly there will be a fatal difference or error because this also involves the success of a company and will be needed when you want to report income and expenses of a company then from it must be careful in the process of recording and analyzing purchase transactions in the form of purchase offers and orders. Considering that these activities are very important for the success of the company, by using online accounting software can facilitate recording and analyzing a series of purchase transactions because they can be accessed anywhere and anytime with an internet connection, thus purchasing transaction reports can be monitored more easily and in the process of recording and analyzing purchase transactions the form of offers and bookings will work more effectively and efficiently. Keywords​: online accounting software, recording, offering and ordering purchases